Changing Fashions in Philosopher-Salesmen - Bronfenbrenner, M. (The Review of Economics and Statistics, 1954)
carried out we shall need a very substantial cut in individual income taxes. What that amount should be must be reached by a process of experimentation. I would lean on the side of bold reductions. We must learn to be prepared to reverse any action in such measure as events prove to be necessary. The President's Economic Report wisely counsels the need to be flexible. Unless the government is prepared to reverse itself, we shall never dare to act promptly and effectively. This is a lesson every member of the Congress needs very much to learn. Our experience since I948 gives proof of the fact that we can stoke an immense amount of fuel into the American economy without producing inflation. Since I948 (despite the Korean explosion) wholesale prices have risen less than i per cent per annum. In the peaceful days before the First World War, wholesale prices rose 3 per cent per annum for a period of I5 years. There is a real danger that we shall be too cautious always fearful of inflation and that in consequence we shall fail to reach even approximately our full production potential. There is also a danger that we shall be dragged down by the dogma of the balanced budget. It is generally agreed that the current ratio of money and liquid assets to GNP is favorable. As our GNP rises, our debt may also be permitted to rise, if that proves to be necessary to promote adequate growth and expansion. It is not improbable that the structural adjustment which is needed to offset the structural deflationary changes currently in process will require a cut in taxes substantially in excess of the cut in federal expenditures.